Measurement of leg preference in 7-year-old children: The effect of task characteristics. - Atun-Einy, Osnat; Farkash, Inna (Laterality, 2026)
The age at which leg preference becomes clearly established in children remains debated, possibly due to inconsistent expression across task types. Leg preference was assessed in 34 right-handed 7-year-olds (53% girls) using a battery of 10 age-appropriate tasks, each performed 10 times with trial independence. Tasks were categorized by bilateral vs. unilateral, movement-leading vs. stabilization, object manipulation, task starting and ending points, and body position. Leg preference was quantified by direction and degree across participants, tasks, and categories, and a general index was computed. Results indicate that 86% of children exhibited a strong right-leg preference. Stronger and more consistent preferences were found in bilateral, movement-leading, and object-manipulation tasks, whereas unilateral stabilization tasks showed weaker, more variable patterns. Significant differences emerged across task categories, but none between sitting and standing. These findings demonstrate that leg preference is well established by age seven in right-handed children, yet its expression remains dynamic and task-dependent. Stronger preferences tend to align with tasks demanding higher coordination and attentional engagement. Findings underscore the importance of using diverse tasks when assessing leg preference. This study offers a rigorous protocol for leg preference assessment and provides a baseline for studies of children with typical development and developmental disorders.